Perchlorate Removal in Microbial Electrochemical Systems With Iron/Carbon Electrodes - Yang, Qiao; Zhang, Fengxiang; Zhan, Jingjing; Gao, Chao; Liu, Minhui (Frontiers in Chemistry, 2019)
Perchlorate removal was tested in the cathode chamber of microbial electrochemical systems (MESs). Dual-chambers MESs were constructed and operated in batch mode with four kinds of cathode materials including Fe/C particles (Fe/C), zero valent iron particles (ZVI), blank carbon felt (CF) and active carbon (AC). Without external energy supply or perchlorate-reducing microbial pre-enrichment, perchlorate (ClO4-) removal could be achieved in the cathode chambers of MESs at different efficiencies. The highest ClO4- removal rates in these reactors were 18.96 (Fe/C, 100 Ω, 2 days), 15.84 (ZVI, 100 Ω, 2 days), 14.37 (CF, 100 Ω, 3 days) and 19.78 mg/L/day (AC, 100 Ω, 2 days). ClO4- degradation products were mainly Cl- and ClO3-, and the total chlorine in the products was lower than the theoretical input. The non-conservation of the total chlorine may be caused by the adsorption and co-precipitation related to the electrode materials. Coulombs and coulombic efficiency calculation showed that electron provided by MESs was partially responsible for ClO4- reduction, for the Fe/C cathode reactors, about a quarter of electron was provided by MESs.